Inovasi Ampas Kopi untuk Meningkatkan Kebersihan Mikrobiologi Air Irigasi yang Tercemar oleh Limbah Basreng - Rina Hidayati Pratiwi; Pina Aprilliani; Shafa Noer (Jurnal Biosilampari : Jurnal Biologi, 2023)
The large number of industries that dispose of waste, such as disposing of factory waste into irrigation waters, makes the quality of the irrigation water decrease. If the irrigation water is polluted then it results in an increase in bacteria, of course it will affect the welfare of the community and farmers. The consequences of this need to be corrected, one of which is by giving coffee grounds. Coffee grounds contain volatile acids which can help degrade bacteria, where these volatile acids can penetrate the bacterial cell walls. The purpose of this study was to determine the inhibitory power of coffee grounds on irrigation water exposed to basreng waste in Sariwangi Village, Tasikmalaya. The samples used were 2 samples with a distance of 20 m each. The method used is using TPC (Total Plate Count) testing. The research results show that giving coffee grounds at a dose of 3.3 g was able to reduce the microbes in irrigation water affected by basreng waste by 26% or an average result for point A of 19,000 and for point B of 28,000. Based on the research, coffee grounds can inhibit or reduce coliform bacteria in irrigation water.